2013
DOI: 10.5009/gnl.2013.7.5.539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Gastrointestinal Diseases in Korean Americans and Native Koreans Undergoing Screening Endoscopy

Abstract: Background/AimsIn South Korea, health check-ups are readily accessible to the public. We aimed to compare the prevalence of upper gastrointestinal (GI) and lower GI diseases in Korean Americans and native Koreans to determine differences and risk factors.MethodsIn total, 1,942 subjects who visited Gangnam Severance Hospital from July 2008 to November 2010 for a health check-up were enrolled. Basic characteristics and laboratory data for the subjects were collected. Esophagogastroduodenoscopy and colonoscopy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…PUD requires endoscopic confirmation, which suggests that some of the subjects in our study may not have had PUD. However, the incidence of endoscopically confirmed PUD has been reported to be between 2–10% in Korea, which suggests that our study may not have overestimated PUD incidence34353637. Also, as the lifetime screening rate for stomach cancer during the study period was about 65%, we believe that many of our subjects had been diagnosed with PUD by endoscopy38.…”
Section: Discussionmentioning
confidence: 67%
“…PUD requires endoscopic confirmation, which suggests that some of the subjects in our study may not have had PUD. However, the incidence of endoscopically confirmed PUD has been reported to be between 2–10% in Korea, which suggests that our study may not have overestimated PUD incidence34353637. Also, as the lifetime screening rate for stomach cancer during the study period was about 65%, we believe that many of our subjects had been diagnosed with PUD by endoscopy38.…”
Section: Discussionmentioning
confidence: 67%
“…Many similar studies have shown the same results. [16][17][18] There is no scientific interpretation regarding the predominance in the male. However, many female patients hesitate to report to the hospital for the treatment of haemorrhoid and thus the recorded prevalence rate is less in them.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that Koreans born in the United States have similar GC risk as native Koreans, with some experts advocating the screening of Asian Americans according to Asian guidelines . However, other studies comparing foreign‐born to US‐born Blacks and Hispanics demonstrate significant differences in incidence, tumor subtypes, and location, suggesting distinct disease entities that rely more on country of origin .…”
Section: Epidemiologymentioning
confidence: 99%
“…Given the significant differences in GC incidence and mortality rates among different racial groups in the United States, targeted screening strategies may be implemented in certain groups. A comparison of gastrointestinal disease prevalence in Korean Americans and native Koreans demonstrated similar rates of GC (0.3% vs 0.4%), suggesting that Korean Americans may benefit from screening more akin to that of the nationwide programs in Asia . Other experts would argue for a one‐time endoscopy at the age of 50 for first‐ or second‐generation immigrants from a high‐incidence region (eg, East Asia, Russia, or South America) .…”
Section: Screening and Surveillancementioning
confidence: 99%